2013
DOI: 10.1111/jfbc.12036
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Quality Parameters, Exopeptidase and Oxidoreductase Activity Changes During Temporal Development of Wheat Grain Infestation by Sitophilus granarius

Abstract: Changes in chemical composition, grain quality parameters, oxidoreductase and exopeptidase activities of wheat grains infested by Sitophilus granarius were monitored during 1 year of storage. Significant increase in flour titratable acidity of infested grains occurred by day 90. Subsequently, infestation was followed by decrease of grain hectoliter weight on day 180, decrease of carboxypeptidase activity on day 240, polyphenol oxidase and catalase activities increased and total starch decreased on day 270, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…However, inadequate control of factors affecting grain quality at this postharvest stage impairs the nutritional quality and technological and sensory properties of the grains, thus, reducing the commercial value (Ferreira et al, , ; Siqueira et al, ; Tulyathan & Leeharatanaluk, ; Ziegler, Ferreira, Hoffmann, Chaves, et al, ). Among the factors that affect grain quality during the storage period are moisture and grain temperature, temperature and relative humidity of the air in the storage environment, quality of the grains shortly after harvesting, and presence of insects (Nasar‐Abbas et al, ; Njoroge et al, ; Pohndorf, Meneghetti, Paiva, Oliveira, & Elias, ; Rani, Chelladurai, Jayas, White, & Kavitha‐Abirami, ; Strelec, Šarkanj, Mrša, & Ugarcic‐Hardi, ). Controlling these factors provides the lowest rates of metabolic activity in the grains during storage, and lower is the respiratory rate, lower is the consumption of energy reserves, representing their better conservation (Chidananda et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inadequate control of factors affecting grain quality at this postharvest stage impairs the nutritional quality and technological and sensory properties of the grains, thus, reducing the commercial value (Ferreira et al, , ; Siqueira et al, ; Tulyathan & Leeharatanaluk, ; Ziegler, Ferreira, Hoffmann, Chaves, et al, ). Among the factors that affect grain quality during the storage period are moisture and grain temperature, temperature and relative humidity of the air in the storage environment, quality of the grains shortly after harvesting, and presence of insects (Nasar‐Abbas et al, ; Njoroge et al, ; Pohndorf, Meneghetti, Paiva, Oliveira, & Elias, ; Rani, Chelladurai, Jayas, White, & Kavitha‐Abirami, ; Strelec, Šarkanj, Mrša, & Ugarcic‐Hardi, ). Controlling these factors provides the lowest rates of metabolic activity in the grains during storage, and lower is the respiratory rate, lower is the consumption of energy reserves, representing their better conservation (Chidananda et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…. Among the factors that affect grain quality during the storage period are moisture and grain temperature, temperature and relative humidity of the air in the storage environment, quality of the grains shortly after harvesting, and presence of insects (Nasar-Abbas et al, 2009;Njoroge et al, 2015;Pohndorf, Meneghetti, Paiva, Oliveira, & Elias, 2018;Rani, Chelladurai, Jayas, White, & Kavitha-Abirami, 2013;Strelec, Šarkanj, Mrša, & Ugarcic-Hardi, 2013). Controlling these factors provides the lowest rates of metabolic activity in the grains during storage, and lower is the respiratory rate, lower is the consumption of energy reserves, representing their better conservation (Chidananda et al, 2014).…”
mentioning
confidence: 99%
“…For determination of the extractable protein content and activity of oxidoreductive and proteolytic enzymes, it was necessary to extract proteins and enzymes from differently stored grains. Extractions were performed by Strelec et al [28]. Extractable protein content was determined using the Bradford method [29] with bovine serum albumin as standard.…”
Section: Extractable Protein Content Peptidase and Oxidoreductase Act...mentioning
confidence: 99%
“…Carboxypeptidase activity was determined using the colorimetric method using N-carbobenzyloxy-L-phenylalanyl-leucine (CBZ-Phe-Leu) as substrate and picrylsulfonic acid as hydrolysis product coupler, according to Waters et al [32]. Aspartic proteinase activity was measured using 2% (w/v) Hb as substrate according to Voigt et al [33] with some modification previously reported by Strelec et al [28]. Catalase activity was determined using a colorimetric assay using a catalase assay kit (Sigma, USA).…”
Section: Extractable Protein Content Peptidase and Oxidoreductase Act...mentioning
confidence: 99%
“…Essas diferenças são atribuídas à perda ou ganho de umidade durante as etapas de expurgo, catação manual de sementes brocadas e tratamento com fungicida. Devido à sua higroscopicidade, as sementes são propensas à troca de umidade com o ar circundante (Strelec et al, 2010). Apesar disso, os teores de água permaneceram próximos aos teores de água final após a secagem.…”
Section: Teor De áGuaunclassified